Formation en agro-écologie - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Le Centre écologique Albert Schweitzer organise, en septembre 2000, une formation à la lutte phytosanitaire en agro-écologie.Centre écologique Albert Schweitzer01 BP 3306, Ouagadougou 01 BURKINA FASOFax : + 226 34 10 65E-mail : ceas-rb@fasonet.bf